PENGARUH HASIL BELAJAR KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA KELAS XI SMK PANCA BHAKTI KUBU RAYA - Rhosa, Eliya; Sulistyarini, Sulistyarini; Sumartono, Bambang Genjik (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe title of this research is the Effect of Learning Outcomes of Entrepreneurship on Entrepreneurial Interest in Class XI Students of SMK Panca Bhakti Sungai Raya Kubu Raya Regency. A general problem in this study is how the effect of entrepreneurial learning outcomes on entrepreneurial interest in class XI students of SMK Panca Bhakti Sungai Raya, Kubu Raya Regency. The purpose of this study was to determine the learning outcomes of entrepreneurship subjects in class XI Vocational High School Panca Bhakti Sungai Raya, to determine the entrepreneurial interest of students in class XI Vocational School Panca Bhakti and to determine the effect of entrepreneurial learning outcomes on entrepreneurial interest in class XI Vocational School Panca Bhakti. The method used is a descriptive method with the form of a study of relationship studies that aims to determine the effect of entrepreneurial learning outcomes on student entrepreneurial interest. The results of this study stated that the effect of entrepreneurial learning outcomes on student entrepreneurial interest in the amount of 26.7% included in the low category and the remaining 73.3% was influenced by other factors such as motivation and background of students' parents who were not reviewed in this study.Â Keywords:Learning Outcomes, Entrepreneurship Interest